Hypoparasitic fungus tuberculina persicina (DITM. EX fR.) Sacc., as biocontrol agent for rusts - Shamsi, Shamim; Naher, Najmun (Dhaka University Journal of Biological Sciences, 2011)
Key words: Tuberculina persicina; Hyperparasitic; Biocontrol agent; Rusts DOI: http://dx.doi.org/10.3329/dujbs.v19i1.8950 DUJBS 2010; 19(1): 99-102